Effects of steel slag as fine aggregate on static and impact behaviours of concrete. (20th December 2018) - Guo, Yongchang; Xie, Jianhe; Zheng, Wenyu; Li, Jianglin
Highlights: The impact behaviour of SSC was studied under SHPB compression. The addition of steel slag doesn't linearly contribute to the static and dynamic compressive strength of SSC. The suggested optimum content of steel slag as fine aggregate is 20% for SSC. Abstract: The use of steel slag as aggregate in concrete is a sustainable solution for reducing serious impact on the ecological environment caused by the shortage of natural mineral resources. This paper presents the first ever study on the behaviour of steel slag sand concrete (SSC) under axial impact compression. Results from a series of cylinder tests under monotonic and impact compression using SSCs incorporated with steel slag by 0%, 10%, 20%, 30% and 40% volume substitution of fine aggregate are presented and discussed. The results show that the addition of steel slag as fine aggregate can improve the static and dynamic compressive strength of concrete; the compressive strength of the SSC subjected to impact loading first increases and then decreases with increase in the steel slag content, similar to that of SSC under monotonic compression. Furthermore, the incorporation of steel slag into concrete results in increased stiffness and brittleness; however, the failure mode of SSC under impact loading is similar to that of normal concrete. To obtain improved performance for SSC subjected to monotonic and impact compression, the suggested optimum content of steel slag as fine aggregate is 20%.